1994
DOI: 10.1093/nar/22.6.1068
|View full text |Cite
|
Sign up to set email alerts
|

Direct selection of binding proficient/catalytic deficient variants ofBamHI endonuclease

Abstract: Variants of BamHl endonuclease in which the glutamate 1 13 residue has been changed to lysine or the aspartate 94 to asparagine were shown to behave as repressor molecules in vivo. This was demonstrated by placing a BamHl recognition sequence, GGATCC, positioned as an operator sequence in an antisense promoter for the aadA gene (spectinomycin resistance). Repression of this promoter relieved the inhibition of expression of spectinomycin resistance. This system was then used to select new binding proficient/cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…A recent report indicates that EcoRV can bind to DNA in the absence of Ca 2ϩ or Mg 2ϩ under different conditions (44); attempts to visualize a gel shift for PvuII in the absence of metal ions or in the presence of Mg 2ϩ for the catalytically inactive mutants have thus far been unsuccessful. Similar mutagenesis studies have been done on EcoRI (10 -13, 15, 45), EcoRV (18,20,23,24,28), and BamHI (26,27,30). These studies have anticipated or confirmed the predicted roles of residues identified as central from the crystal structures of the respective enzymes.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…A recent report indicates that EcoRV can bind to DNA in the absence of Ca 2ϩ or Mg 2ϩ under different conditions (44); attempts to visualize a gel shift for PvuII in the absence of metal ions or in the presence of Mg 2ϩ for the catalytically inactive mutants have thus far been unsuccessful. Similar mutagenesis studies have been done on EcoRI (10 -13, 15, 45), EcoRV (18,20,23,24,28), and BamHI (26,27,30). These studies have anticipated or confirmed the predicted roles of residues identified as central from the crystal structures of the respective enzymes.…”
Section: Discussionmentioning
confidence: 62%
“…There is a relative paucity of mutations described similar to, for example, T37A of EcoRV (28) that are located outside the catalytic domain and bind DNA specifically but are defective in cleavage. In one case where catalytic mutations of BamHI were selected directly using the transcriptional interference method, all the mutations found were in catalytic domain residues (26). This rarity may be due to how the mutations were made and analyzed rather than a reflection of their abundance in nature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations